Orientation dependence of damping behavior in a Mn-Cu shape memory alloy. (September 2019) - Zuo, Shungui; Xiao, Fei; Fukuda, Takashi
Abstract: Internal friction of a Mn-11Cu (at.%) alloy was studied in the main [001], [011] and [111] crystallographic directions by applying tensile stress. Two internal friction peaks were observed in three directions. One is twin boundary-related relaxation peak (in the temperature range of 200–300 K), which is highest in the [001] direction and lowest in the [111] direction. Other is associated with reverse martensitic transformation (~430 K), and its orientation dependence is small. The orientation dependence of the twin boundary-related internal friction peak is discussed based on the Schmid factor for the movement of {011} twin boundaries. Graphical abstract: Unlabelled Image